Initiative de recherche sur les arts autochtones: rapport des consultations - Trépanier, France; Conseil des arts du Canada (Conseil des arts du Canada, 2008)
Le présent document est un rapport sur la série de consultations tenues en 2007 avec des artistes, des administrateurs des arts, des aînés, des jeunes et d’autres membres de la communauté autochtone. Cette série de consultations a eu lieu dans le cadre de l’initiative de recherche sur les arts autochtones, mise sur pied dans le but de planifier et d’entreprendre les travaux de recherche nécessaires pour appuyer et orienter le plan d’action sur les arts autochtones du Conseil des arts du Canada.
Keywords: 1-Histoire de l'art; 2-Méthodologie de recherche décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Native Studies Keywords - Teves, Stephanie N.; Smith, Andrea; Raheja, Michelle H. (Critical issues in indigenous studies, 2015)
"Native Studies Keywords explores selected concepts in Native studies and the words commonly used to describe them, words whose meanings have been insufficiently examined. This edited volume focuses on the following eight concepts : sovereignty, land, indigeneity, nation, blood, tradition, colonialism, and indigenous knowledge. Each section includes three or four essays and provides definitions, meanings, and significance to the concept, lending a historical, social, and political context. Take sovereignty, for example. The word has served as the battle cry for social justice in Indian Country. But what is the meaning of sovereignty? Native peoples with diverse political beliefs all might say they support sovereignty-without understanding fully the meaning and implications packed in the word. The field of Native studies is filled with many such words whose meanings are presumed, rather than articulated or debated. Consequently, the foundational terms within Native studies always have multiple and conflicting meanings. These terms carry the colonial baggage that has accrued from centuries of contested words. Native Studies Keywords is a genealogical project that looks at the history of words that claim to have no history. It is the first book to examine the foundational concepts of Native American studies, offering multiple perspectives and opening a critical new conversation"--Résumé du site web de l'éditeur
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Whose Land Is It Anyway?: A Manual for Decolonization - McFarlane, Peter; Schabus, Nicole (Fédération of Post-Secondary Education of BC, 2018)
Whose Land Is It Anyway? A Manual for Decolonization provides a variety of Indigenous perspectives on the history of colonialism, current Indigenous activism and resistance, and outlines the path forward to reconciliation. This audio version features renowned Indigenous writers Taiaiake Alfred, Glen Coulthard, Russell Diabo, Beverly Jacobs, Melina Laboucan-Massimo, Kanahus Manuel, Jeffrey McNeil-Seymour, Pamela Palmater, Shiri Pasternak, Nicole Schabus, Senator Murray Sinclair, and Sharon Venne. The late Arthur Manuel’s writings are read by his grandson, Mahekan Anderson.
Keywords: 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Danser sur le dos de notre tortue = Niimtoowaad mikinaag gijiying bakonaan: nouvelle émergence des Nishnaabeg - Simpson, Leanne (Collection Proses de combat, 2018)
On parle beaucoup au Québec, comme dans le reste du Canada, de réconciliation avec les Premières Nations. Mais pour qu'un rapprochement fécond puisse avoir lieu, qu'une nouvelle ère, égalitaire et respectueuse, s'ouvre, le cadre constitutionnel canadien ne peut à lui seul en définir les règles. Toute entente devra aussi tenir compte des traditions autochtones. C'est dans ce contexte que le livre de Leanne Simpson trouve toute sa pertinence. L'auteure s'y demande comment redonner force, consistance et valeur à un héritage politique, juridique et culturel mis à mal par le processus colonial. D'une façon aussi concrète que tonique et audacieuse, elle y explore la langue, les mythes, les coutumes et les expériences de sa culture ancestrale afin de recouvrer et révéler cette manière singulière et originale d'être au monde trop longtemps méprisée. Si l'entreprise est inspirante pour toute communauté issue des Premières Nations, elle l'est également pour quiconque s'intéresse aux contradictions de la modernité occidentale. -- [Renaud-Bray]
Keywords: 2-Méthodologie de recherche décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Decolonizing Methodologies: Research and Indigenous Peoples - Tuhiwai Smith, Linda (Zed books, 2012)
To the colonized, the term 'research' is conflated with European colonialism; the ways in which academic research has been implicated in the throes of imperialism remains a painful memory. This essential volume explores intersections of imperialism and research - specifically, the ways in which imperialism is embedded in disciplines of knowledge and tradition as 'regimes of truth.' Concepts such as 'discovery' and 'claiming' are discussed and an argument presented that the decolonization of research methods will help to reclaim control over indigenous ways of knowing and being. Now in its eagerly awaited third edition, this bestselling book includes a co-written introduction features contributions from indigenous scholars on the book's continued relevance to current research. It also features a chapter with twenty-five indigenous projects and a collection of poetry
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Decolonization is not a Metaphor - Tuck, Eve; K. Wayne Yang (Journal Publishing Services, 2012)
Our goal in this article is to remind readers what is unsettling about decolonization. Decolonization brings about the repatriation of Indigenous land and life; it is not a metaphor for other things we want to do to improve our societies and schools. The easy adoption of decolonizing discourse by educational advocacy and scholarship, evidenced by the increasing number of calls to “decolonize our schools,” or use “decolonizing methods,” or, “decolonize student thinking”, turns decolonization into a metaphor. As important as their goals may be, social justice, critical methodologies, or approaches that decenter settler perspectives have objectives that may be incommensurable with decolonization. Because settler colonialism is built upon an entangled triad structure of settler-native-slave, the decolonial desires of white, non-white, immigrant, postcolonial, and oppressed people, can similarly be entangled in resettlement, reoccupation, and reinhabitation that actually further settler colonialism. The metaphorization of decolonization makes possible a set of evasions, or “settler moves to innocence”, that problematically attempt to reconcile settler guilt and complicity, and rescue settler futurity. In this article, we analyze multiple settler moves towards innocence in order to forward “an ethic of incommensurability” that recognizes what is distinct and what is sovereign for project(s) of decolonization in relation to human and civil rights based social justice projects. We also point to unsettling themes within transnational/Third World decolonizations, abolition, and critical space-place pedagogies, which challenge the coalescence of social justice endeavors, making room for more meaningful potential alliances
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

First Person Plural: Aboriginal Storytelling and the Ethics of Collaborative Authorship - McCall, Sophie (UBC Press, 2011)
Told-to narratives, or collaboratively produced texts by Aboriginal storytellers and (usually) non-Aboriginal writers, often confound traditional literary understandings of voice and authorship. In this innovative exploration, these unique narratives are not romanticized as unmediated translations of oral documents, nor are they dismissed as corruptions of original works. Rather, the approach emphasizes the interpenetration of authorship and collaboration. Discussing a wide range of told-to narratives, including ethnography, recorded (auto)biography, testimonial life narrative, documentary, myth, legend, and song, Sophie McCall explores the multifaceted implications of the choices that editors, translators, narrators, and filmmakers make as they channel these narratives into new forms. Focused on the 1990s, when debates over voice and representation were particularly explosive, this comprehensive study examines collaboratively produced texts in conjunction with key political events that have shaped the struggle for Aboriginal rights in Canada. Emphasizing the scope rather than the limits of the told-to narrative, McCall considers how Aboriginal voices have been represented in a range of forums such as public inquiries, commissioners’ reports, and land claims court cases. A captivating inquiry, First Person Plural offers a vital, interdisciplinary discussion of how told-to narratives contribute to larger debates about Indigenous voice and literary and political sovereignty. This innovative, interdisciplinary study will be of interest to students and scholars of Indigenous studies, textualized oral narrative, literary studies, and Canadian cultural studies
Keywords: 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Reclaiming Indigenous Voice and Vision - Battiste, Marie. (UBC Press, 2000)
This book seeks to clarify postcolonial Indigenous thought beginning at the new millennium. It represents the voices of the first generation of global Indigenous scholars and converges those voices, their analyses, and their dreams of a decolonized world.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Indigenous Methodologies: Characteristics, Conversations, and Contexts - Kovach, Margaret (University of Toronto Press, 2009)
"An innovative and important contribution to Indigenous research approaches, this revised second edition provides a framework for conducting Indigenous methodologies, serving as an entry point to learn more broadly about Indigenous research."--
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé